Investigation of stability electron beam parameters in sources with cold secondary-emission cathodes - Dovbnya, A.N.; Ayzatsky, N.I.; Boriskin, V.N.; Zakutin, V.V.; Kushnir, V.A.; Mitrochenko, V.A.; Reshetnyak, N.G. (Вопросы атомной науки и техники, 2004)
The investigation into the generation of tubular electron beams and their parameters in a system of secondaryemission cathodes was carried out. The parameters of electron beams with the use of a multichannel measuring system were measured. In the 8-cathode system at a cathode voltage of ~34 kV and a magnetic field strength of
~3500 Oe the total current of all beams was ~35 A and its stability was 4...5%. In the single magnetron gun at a cathode voltage of ~30 kV and a magnetic field strength of ~2500 Oe the beam current was ~60 A. And its stability was
2...4%. Проведено дослідження генерації та параметрів трубчатих електронних пучків в системі
вторинноемісійних катодів. Проведено вимірювання параметрів електронних пучків з допомогою
багатоканальної вимірюваної системи. В 8-мі катодній системі при напрузі на катодах ∼34 кВ і
напруженості магнітного поля ∼3500 Ое загальний струм пучків був ∼35 А, а стабільність ∼4…5%. В
одиночній магнетронній гарматі при напрузі на катоді ∼30 кВ і напруженості магнітного поля ∼2500 Ое
струм був ∼60 А, а стабільність ∼2…4%. Проведено исследование генерации и параметров трубчатых электронных пучков в системе вторичноэмиссионных катодов. Измерены параметры электронных пучков с помощью многоканальной измерительной системы. В 8-ми катодной системе при напряжении на катодах ∼34 кВ и напряженности магнитного
поля ∼3500 Ое суммарный ток всех пучков составлял ∼35 А., а его стабильность составляет ∼4…5%. В одиночной магнетронной пушке при напряжении на катодах ∼30 кВ и напряженности магнитного поля ∼ 2500 Ое ток пучка составлял ∼60 А., а его стабильность составляет ∼2…4%.